2020
DOI: 10.18535/ijsshi/v7i01.01
|View full text |Cite
|
Sign up to set email alerts
|

Remuneration as a tool for increasing Employee Performance in Nigerian

Abstract: This research work assesses fundamentally remuneration as a device for expanding employee performance with specific reference to Bottling Companies in Nigeria. The broad aim of this research is to decide the role of remuneration in expanding workers performance. The population of the study is 200. The study adopt primary and secondary sources to gather information and copies of questionnaire were used also. The research adopted survey and descriptive research technique in analyzing data acquired from Bottling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The goal is to boost morale and output by providing incentives to workers in the form of monetary benefits and others. Onyekwelu et al (2020), posited that an entity's financial success is directly tied to the quality of the benefits and welfare it offers its workers. To back up the aforementioned claim, Mensah et al (2017), found that employees' dedication and output are boosted when their employers demonstrate genuine concern for their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to boost morale and output by providing incentives to workers in the form of monetary benefits and others. Onyekwelu et al (2020), posited that an entity's financial success is directly tied to the quality of the benefits and welfare it offers its workers. To back up the aforementioned claim, Mensah et al (2017), found that employees' dedication and output are boosted when their employers demonstrate genuine concern for their well-being.…”
Section: Introductionmentioning
confidence: 99%